Solubilização e efeito de tapsigargina em Ca2+-ATPase de larva de Pachymerus nucleorum (Fabricius 1792) (Coleoptera: Chrysomelidae: Bruchinae) - Duarte, Vinícius Luis (2007)
CHAPTER I: Pachymerus nucleorum Fabricius 1792 is a beetle specie that predate babaçu coconut (Orbignya sp.). It belong to Bruchinae coleoptera subfamily, whose representants are know as seed bits. We found a precipitated fraction from larvae of P. nucleorum that is not solubilized by Triton X-100 (P3) and presents Ca2+-ATPase and K+/EDTA-ATPase activity. The objective of this work was solubilize and characterize the enzyme responsible for the Ca2+-ATPase activity. The Ca2+-ATPase was partially solubilized with 600 mM NaCl and the soluble fraction from this assay (S4) was better characterized. We noticed in SDS-PAGE a strongly stained polypeptide with 205 kDa and two others with 130 and 102 kDa. 600 mM NaCl inhibits about 40% of P3 Ca2+-ATPase activity, and 84% with 2 M NaCl. We found in S4 Mn2+-ATPasic activity, corresponding to 40% of the observed with calcium, and no Mg2+-ATPase activity was detected. In presence of Zn2+ or Fe2+ the ATPase activity was null and when incubated with cobalt, copper, barium, litium or Fe 2+, the ATPase activity correspond to less than 20% of the Ca2+-ATPase activity. The Ca2+- ATPase activity was completely inhibited by magnesium, copper ou zinc. Cobalt, manganese, Fe3+ or Fe2+ inhibited in more than 60% such activity, and barium and litium didn t affect the calcium-dependent activity. In this work, the Ca2+-ATPase activity of Pachymerus nucleorum larvae was partially solubilized with 600 mM NaCl and presents Ca2+-ATPase activity inhibited by magnesium. CHAPTER II: Ca2+-ATPases are ATPases involved in transport of calcium across membranes. Sarcoplasmic and endoplasmic Ca2+-ATPases are irreversibly inhibited by thapsigargin in micromolar concentrations. The objective of this work was to test the effect of thapsigargin on Ca2+-ATPase activity isolated from Pachymerus nucleorum larvae, a beetle especie that belongs to Bruchinae coleoptera subfamily. The P. nucleorum larvae were homogeneized and the precipitated fraction (P3 fraction) not solubilized with Triton X-100 was used to thapsigargin inhibtion tests. Thapsigargin 140 μM inhibit about 80% and 90% of Ca2+-ATPase activity of P3, when added in the begin or 5 minutes before the start reaction, respectivelly. Preincubation with ATP or calcium partially prevented the inhibition of Ca2+-ATPase activity. The inhibition was completely prevented with pre-incubation with both ATP e calcium. The results showed in this work suggest that the ATPase isolated from P. Nucleorum larvae treats of a Ca2+-ATPase.